INTEGRASI KECERDASAN BUATAN DALAM PENDIDIKAN BERBANTUAN APLIKASI AI - Meriyanti Meriyanti (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
The integration of Artificial Intelligence (AI) in education has significantly enhanced learning experiences by providing personalized learning, intelligent tutoring systems, and automated assessments. AI-powered applications help students understand concepts more effectively and assist educators in administrative tasks. The benefits of AI in education include adaptive learning, real-time feedback, and increased accessibility. However, challenges such as data privacy, ethical concerns, and technological infrastructure must be addressed. This paper explores the implementation, benefits, challenges, and future prospects of AI-assisted education applications.